Evaluating the relative importance of different blood pressure indices in screening for NAFLD: a survey report based on a health examination population - Hu, Chong; Yu, Ziqi; Wei, Changli; Sheng, Guotai; Chen, Jianyong; Zou, Yang (Frontiers in Cardiovascular Medicine, 2024)
Objective While hypertension is a well-recognized risk factor for non-alcoholic fatty liver disease (NAFLD), the specific roles of various common blood pressure measurements [diastolic blood pressure (DBP), systolic blood pressure (SBP), pulse pressure (PP), mean arterial pressure (MAP)] in detecting NAFLD and evaluating the associated risk in adults remain unclear. Methods A retrospective analysis was conducted on 14,251 adult participants undergoing health screenings in the NAfld in the Gifu Area, Longitudinal Analysis project (NAGALA). Following the Z-transformation of the independent variables, we evaluated the relationships between the four blood pressure indices and NAFLD through multivariable logistic regression models. This analysis documented the odds ratio (OR) and 95% confidence interval (CI) for each standard deviation (SD) increase. Additionally, the effectiveness of these indices in identifying NAFLD was comparatively analyzed using receiver operating characteristic (ROC) curves. Results After adequately adjusting for confounders, all blood pressure indices except PP showed a positive correlation with NAFLD. For each SD increment, MAP had the strongest association with NAFLD compared to SBP and DBP. This finding was confirmed in populations without exercise habits, under 60 years of age, with normal blood pressure, and in non-obese groups. Furthermore, based on ROC analysis, MAP was found to have the highest accuracy in identifying NAFLD compared to the other three blood pressure indices. Conclusion Among the four blood pressure indices evaluated, MAP demonstrates the greatest efficacy in identifying NAFLD and assessing its associated risk. These findings underscore the potential of MAP as the most promising blood pressure index for screening NAFLD.